Efektivitas Citizen Lawsuit dalam memastikan kepatuhan terhadap standar kualitas udara ambien dalam perizinan usaha : Studi kasus pencemaran sludge di Bandung Tahun 2019 - safitri, mahardini ika (Maliki Interdisciplinary Journal, 2023)
Ambien air pollution due to industrial activities can have a negative impact on public health. In order to ensure company compliance with Ambien Air Quality Standards (SKUA) in business licensing, Citizen Lawsuit can be an effective alternative. This study aims to evaluate the effectiveness of the Citizen Lawsuit in ensuring company compliance with SKUA standards in business licensing, with a case study of air quality sludge pollution in Bandung in 2019. This research is a normative juridical research aimed at studying laws and regulations. The results of the study show that Citizen Lawsuit can be an effective tool to ensure compliance with SKUA audits in business licenses. This can be seen from the lawsuits filed by residents against three companies that are suspected of causing ambient air pollution. As a result, the company was required to pay fines and improve its waste management system. However, there are obstacles in implementing citizen claims such as difficulties in gathering evidence, institutional limitations, and high costs. There needs to be greater attention to legal support and NGOs to monitor and ensure that companies run their business responsibly and comply with the rules that have been set.